Visible Light‐Promoted Three‐Component Carboazidation of Unactivated Alkenes with TMSN3 and Acrylonitrile2. Issue 11 (14th September 2018) - Yang, Bo; Ren, Xiang; Shen, Xuzhong; Li, Tongtong; Lu, Zhan
Abstract: A novel difunctionalization of unactivated alkenes has been reported via visible light‐promoted three‐component carboazidation using TMSN3 and acrylonitrile as partners without any stoichiometric oxidants. This protocol is operationally simple for straightforward access to azido derivatives with good functional group tolerance from readily available starting materials. A facile azido radical‐catalyzed [3 + 2] cycloaddition reaction of vinylcyclopropane with acrylonitrile was also observed to deliver a multi‐substituted cyclopentane. Abstract : Visible light‐promoted three‐component carboazidation of unactivated alkenes using TMSN3 and acrylonitrile as reaction partners without any stoichiometric peroxides was reported. The intramolecular reaction of 1, 6‐diene could also undergo smoothly to afford the cyclization product. The obtained δ‐azido alkylnitriles could be readily converted into valuable building blocks for medicinal chemistry and organic synthesis. A facile azido radical initiated [3 + 2] cycloaddition reaction of vinylcyclopropane with acrylonitrile was also observed to deliver a substituted cyclopentane.